Overview of assessment for deaf and hard of hearing students. Issue 3 (12th November 2019) - Neild, Raschelle; Fitzpatrick, Michael
Abstract: Historically assessing deaf and hard of hearing (D/HH) students has been a daunting challenge. Although significant strides have been made, there continues to be a dearth of research and literature specifically addressing the endemic challenges multidisciplinary teams encounter when assessing D/HH students. This article delineates a historical overview, purpose of assessment, student‐centered approaches, limitations and challenges, and appropriate protocols for assessing D/HH students.